THE PHENOMENON OF CHILDFREE AS A CULTURE THAT CONTRADICTS PATRIARCHAL IDEOLOGY IN INDONESIA - Allecya Nor Malita Sari; Rini Fidiyani (Law Research Review Quarterly, 2025)
Based on the National Socioeconomic Survey conducted by the Central Statistics Agency in 2022, 8% of Indonesian women (equivalent to 71,000 people) aged 15-49 chose to be childfree. This phenomenon is considered deviant from norms, religion, and culture. In addition, it also has a negative impact on the population and the existence of the country. This study aims to identify and analyze the causes of childfree in Indonesia and the government's response to this phenomenon. The research method used is sociological-legal with a qualitative approach. The results of the study indicate that childfree in Indonesia is caused by internal and external cultural impacts, economic and psychological factors, environmental and demographic issues, technological development, and reproductive health. Government actions to anticipate the spread of the childfree movement include developing programs that enhance family resilience and well-being. This study employs Schutz's phenomenological theory, gender theory (nature, nurture, and equilibrium), and James E. Anderson's public policy theory. Schutz's phenomenological theory helps understand the meaning of childfree for its adherents as an expression of individual freedom perceived to bring happiness. Gender theory explains the relationship between patriarchy and childfree. Patriarchy emerges from the nature approach, while childfree from nurture. Gender equilibrium theory serves as a mediating solution by balancing individual rights and social interests. James E. Anderson's public policy theory is used to assess the urgency of the issue and formulate relevant policies.